(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
Durban is known for its multiculturalism; the British Colonial Influence and the impact of the Indian settlers due to indenture and business opportunity. Tourism is rife due to the favourable climate, extensive beaches and wide spread of food. The architectural value of Durban has not, however, been adequately documented. While the multiple identities in the built form has been documented, the architectural narratives that Durban expresses, between different parts of the city up to the waterfront requires much more exposure. This paper traces and analyses the architectural narratives of Durban via a metaphoric journey through space and time.